The thinking executive's guide to sustainability - Kassel, Kerul (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
We live in an increasingly global economy in which the effects of shrunken economies, broadened communication, and widespread meteorological incidents associated with climate change are leaving virtually no one untouched. As a result, a working knowledge of concepts such as the triple bottom line and sustainability have become mandatory. Systems thinking, foundational for grasping these concepts, is based on transdisciplinary theories, deriving in part from biology, physics, economics, philosophy, computer science, engineering, geography, and other sciences. Specifically it is the study of systems, including all life-forms, climate phenomena, and even in human learning and organizational processes, that regulate themselves through feedback.
1. Systems simplified -- 2. What is meant by sustainability and who defines it -- 3. Systems and sustainability -- 4. Commerce as a system -- 5. Why industry is crucial to sustainability -- 6. Corporate sustainability frameworks, metrics, and indices -- 7. Where to start in your business -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 157-170) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF title page (viewed on January 3, 2014).
Keywords: Sustainability; Social responsibility of business; corporate sustainability; corporate social responsibility; corporate citizenship; stakeholder management; sustainable business; green business practices; metrics options